Prion - A Review - Nehete, Minakshi (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACT Prion diseases are incurable neurodegenerative diseases caused by proteinaceous infectious particles affecting both animals and humans. Human prion diseases include Creutzfeldt-Jakob disease (CJD), Kuru, Gerstmann-Sträussler-Scheinker Disease (GSS), Fatal Familial Insomnia (FFI), Variant Creutzfeldt-Jakob Disease (vCJD). The spread of human prion diseases is through ingestion of contaminated meat. Animal prion diseases like scrapie of sheep, transmissible mink encephalopathy, chronic wasting disease of cervids, and bovine spongiform encephalopathy all seem to be laterally transmitted by contact with infected animals or by consumption of infected feed. There is no current treatment for prion diseases. The different modes of transmission of different prion diseases, the unpredictable species barriers, the variable distribution of infectivity in tissues, and strain variations found in some diseases all make risk assessment and predictions of future events difficult. Key Words: Prion, Kuru, Mad cow diseases.